Subclinical Hyperthyroidism Could Predict Poor Outcomes in Patients With Acute Ischemic Stroke Treated With Reperfusion Therapy - Lee, Sang-Hwa; Jang, Min Uk; Kim, Yerim; Park, So Young; Kim, Chulho; Kim, Yeo Jin; Sohn, Jong-Hee (Frontiers in Neurology, 2019)
Background: Evidence for the effect of subclinical thyroid dysfunction on the prognosis of patients suffering from acute ischemic stroke and receiving reperfusion therapy remains controversial. We aimed to investigate the association between subclinical thyroid dysfunction and the outcomes of patients with acute ischemic stroke who were treated with reperfusion therapy. Methods: One hundred fifty-six consecutively recruited patients with acute ischemic stroke receiving reperfusion therapy (intravenous thrombolysis, intraarterial thrombectomy and combined intravenous thrombolysis and intraarterial thrombectomy) were included in this prospective observational study. We divided patients with subclinical thyroid dysfunction into the following 2 groups and defined a euthyroid group: subclinical hyperthyroidism (a thyroid-stimulating hormone level <0.35 μU/mL), subclinical hypothyroidism (a thyroid-stimulating hormone level >4.94 μU/mL), and a euthyroid state (0.35 μU/mL≤thyroid-stimulating hormone level≤4.94 μU/mL). Patients with overt thyroid dysfunction were excluded. The primary outcome was functional disability at 3 months (modified Rankin Scale, mRS), and the secondary outcome was successful reperfusion. A multivariate analysis was performed to evaluate the associations between subclinical thyroid dysfunction and the primary and secondary outcomes. Results: The subclinical hyperthyroidism group appeared to have poor functional outcomes, but the differences were not significant. However, compared with patients in the euthyroid state, patients with subclinical hyperthyroidism had an increased risk of poor functional outcomes at 3 months after a stroke (adjusted odds ratio [OR] 2.50, 95% confidence interval [CI] 1.01-6.14 for a mRS score of 3 to 6) and a decreased rate of successful reperfusion after reperfusion therapy (OR 0.13, 95% CI 0.04-0.43). Conclusion: Subclinical hyperthyroidism may be independently associated with a poor prognosis at 3 months and unsuccessful reperfusion in patients with acute ischemic stroke receiving reperfusion therapy.